2008
DOI: 10.1097/aln.0b013e3181862a0d
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Biopsy and In Vitro  Contracture Test in Subjects with Idiopathic HyperCKemia

Abstract: The evidence of malignant hyperthermia susceptibility by in vitro contracture test seems to be relatively infrequent among subjects with idiopathic hyperCKemia, but the incidence of true malignant hyperthermia in idiopathic hyperCKemia is unknown. Muscle biopsy should be considered a useful, though not very sensitive, diagnostic tool in idiopathic hyperCKemia, because it enables potentially treatable disorders, such as inflammatory myopathies, to be discovered. No uniform morphologic finding typical of idiopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…Of note, the p.Asp4505His variant has been previously implicated in a fatal non-pharmacologic induced MH episode, late-axial myopathy, and idiopathic hyperCKemia with MHS [20, 41, 44]. This reinforces the importance of detecting RYR1 variants, even in those with only mild myopathy-related symptoms, as such individuals can still be at risk.…”
Section: Discussionmentioning
confidence: 71%
“…Of note, the p.Asp4505His variant has been previously implicated in a fatal non-pharmacologic induced MH episode, late-axial myopathy, and idiopathic hyperCKemia with MHS [20, 41, 44]. This reinforces the importance of detecting RYR1 variants, even in those with only mild myopathy-related symptoms, as such individuals can still be at risk.…”
Section: Discussionmentioning
confidence: 71%
“…Weglinski et al (28) reported that 49% of 49 patients with high CK levels had a positive CHCT. However, Malandrini et al (29) described only one MHS and one MHE patient of 37 with idiopathic hyperkalemia, or elevated serum CK levels without weaknesses or other neuromuscular symptoms. CK levels above normal (25-170 U/L) were observed in 13/104 (12.5%) and 25/90 (27.8%) of MHN and MHS patients, respectively, indicating a lack of correlation of CK levels with MH susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Electromyography and nerve conduction studies detect abnormalities in nearly half of cases of asymptomatic CK elevation, 7,21,27,28,30,31,33 but, as with biopsy, most changes are nonspecific. Although electro-myography and nerve conduction studies can help distinguish primary neuropathic from myopathic disorders, the sensitivity and specificity are low for diagnosis.…”
Section: Muscle Biopsy Electromyography and Nerve Conduction Studiesmentioning
confidence: 99%
“…Using combined muscle biopsy, electromyography, and nerve conduction studies, the likelihood of making a diagnosis in patients with asymptomatic elevated CK is 28% on average (range of studies 4%–79%), 2,7,21,2628,30–32 and findings are nonspecific in 30% to 40% of cases. Findings are normal in about 30% to 40% of cases, which are thus diagnosed as idiopathic asymptomatic elevated CK.…”
Section: Muscle Biopsy Electromyography and Nerve Conduction Studiesmentioning
confidence: 99%